DNMT3b基因在人膀胱癌组织中的表达及与临床预后的相关性 (Nan Fang Yi Ke Da Xue Xue Bao, 2020)
OBJECTIVE: To investigate the expression of DNMT3b in human bladder cancer tissues and its correlation with postoperative survival of patients with bladder cancer. METHODS: Thirty-eight pairs of surgically resected human bladder cancer tissues and adjacent bladder tissues were detected by immunohistochemistry for DNMT3b expression, and the correlations of DNMT3b expression level were analyzed with the patients'age, gender, pathological grade, tumor size, T stage, lymph node metastasis and TNM stages. Kaplan-Meier survival analysis was performed to assess the effect of DNMT3b expression on survival outcomes of the patients. RESULTS: High DNMT3b protein expression was detected in 63.16% of the bladder cancer tissues and in 13.16% of the adjacent tissues (P < 0.05). The expression level of DNMT3b was associated with the pathological grade (P=0.002), tumor size (P < 0.001), T stage (P < 0.001), lymphatic metastasis (P=0.039) and TNM stage (P < 0.001), but not with gender or age of the patients. Multivariate logistic regression analysis showed that the protein expression level of DNMT3b was correlated with tumor size (P=0.008) and TNM grades of the tumor (P=0.042). Kaplan-Meier analysis showed that the patients with a high DNMT3b expression had a significantly shorter overall survival than those with a low DNMT3b expression (P=0.021). CONCLUSION: DNMT3b overexpression in bladder cancer is closely related to such clinicopathological factors as pathological grade, tumor size, T stage, lymphatic metastasis, and TNM stage and a shorter overall survival of the patients, suggesting the potential value of DNMT3b as a prognostic marker and a new therapeutic target for bladder cancer.